Workshop for annual review of Building Resilient Agro-sylvopastoral Systems in West Africa through Participatory Action Research (BRAS-PAR) Project and planning “Partnerships for Scaling Climate-Smart Agriculture (P4S) Phase II - Ky-Dembélé, Catherine; Bayala, Jules (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Building Resilient Agro-sylvo-pastoral Systems in West Africa through Participatory Action Research (BRAS-PAR) is a CCAFS Flagship 2 funded four year (2015-2018) project coordinated by the World Agroforestry (ICRAF) and implemented in collaboration with partners namely national agricultural research institutions (INERA in Burkina Faso, SARI in Ghana, INRAN in Niger and ISRA in Senegal) and the International Union for Conservation of Nature (IUCN in Burkina Faso). BRAS-PAR sought to develop up-scalable technological and social innovations of climatesmart agriculture integrating tree-crop-livestock systems through improved understanding of farmer's perceptions and demands, by addressing barriers to adoption taking into consideration gender and social differentiation. The specific objectives include 1) testing, evaluating and validating with rural communities and other stakeholders, scalable climate-smart models of integrated tree-crop-livestock systems, the dominant farming systems in the region, that include climate-risk management strategies; 2) simulating options for improving water and tree-crop-livestock systems under different climate and socio-economic scenarios using models (WaNuLCAS, SWAT, etc.) for informed decision making; 3) assessing the conditions of success and failure of technological interventions on adaptation to climate change. The work here focus on research that evaluates climate-smart practices and technologies that are defined through participatory identification by multistakeholders in each site. Beyond these sites, the approach capitalizes lessons learnt from on-going climate resilient projects to encourage partners to add missing components to the climate-smart village model or initiate new activities when deemed appropriate. Started in 2015, BRAS-PAR targeted three main outcomes: (i) National agricultural research institutions institutionalize the principles of PAR through integration of non-traditional partners in technologies development to generate wider context specific information to be fed into programs and policies to create the enabling environment for the scaling of CSA technologies; (ii) National extension services, development projects and farmer’s organizations widely disseminate and ensure better access to information on best fit CSA portfolios to cope with climate change; and (iii) The private sector including NGOs (FNGN, Larwaal, ARCAD, Care international), microcredit institutions, agro-dealers, rural radios are scaling up/out relevant CSA portfolios through new incentive programs. This project has ended in December 2018 and the meeting review edthe main achievements. During the same first phase of CCAFS , the project “Partnerships for Scaling (P4S) Climate-Smart Agriculture (P56)” was implemented mainly in East Africa with a focus on supporting countries and partners to plan and program CSA actions. It developed new innovations (e.g., The Compendium and Climate Risk Profiles), refreshed and adapted others (e.g., Climate Wizard, mobile-based monitoring) and collaborated on tools (e.g., Rural Household Multi-Indicator Survey, CSA MRV Profile) to develop a comprehensive set of evidence and information to serve diverse stakeholder needs for situation analysis, targeting and prioritizing, program support and monitoring and evaluation (aka ‘CSA-Plan’, Girvetz et al. 2018). Merging the actions of BRAS-PAR and P4S I to become P4S II was done with the intention to use tools and evidence/lessons learned from the Climate-Smart Villages and other development activities, with existing and new partners through direct scientific support to decision makers (e.g., governments, civil society, and researchers) and capacity building to help bring CSA to scale. The scientific activities will be combined with dedicated communication activities such as photo essays, tweets, blog posts, etc. from field staff and partners to raise the visibility of the project and help show case of its successes in supporting countries and position of ICRAF, CIAT, and CCAFS as the go to research organization for the science of scaling up CSA. The key activity areas of P4S II will be around: supporting CSA investment and programming, de-risking agriculture, digital delivery and monitoring and, communauty based scaling of CSA. The present meeting was thought to plan the new activities around these areas for 2019 and beyond.